Kiberseks in pornografija na internetu - Trček, Franc (Teorija in praksa, 2000)
The authors analyse the attitudes of Slovene internet users to erotics and pornography in the cyberspace. The analysed data were collected by WWW research project "The use of Internet in Slovenia 1998". The analysis focuseson pornography as defined by internet users, their attitudes toward social-pathologic pornographic contents and toward censorship or regulation of such contents.
Keywords: Internet; Pornography; Sexuality; Pornografija; Spolnost; Virtual reality; sexual intercourse; Virtualna resničnost; informacijska tehnologija; information technology; navidezna resničnost; kiberseks; ankete